Sleep disturbance and psychological distress in adult patients with tinnitus - Yi-Lu Li; Yu-Ching Hsu; Cheng-Yu Lin; Jiunn-Liang Wu (Journal of the Formosan Medical Association, 2022)
Background/purpose: Sleep disturbance and psychological distress are among the most prevalent comorbidities of tinnitus. We aimed to clarify the dose–response effects of these phenomena with tinnitus severity. Methods: This study enrolled adult patients with subjective tinnitus for more than 6 months was conducted from January 2017 to December 2018 in one tertiary medical center and one local hospital. Data collected included demographic data and questionnaires, namely Tinnitus Handicap Inventory (THI), Pittsburgh Sleep Quality Index (PSQI), Epworth Sleepiness Scale (ESS), and Hospital Anxiety and Depression Scale (HADS). Results: In total, 1610 patients with tinnitus (1105 male, 68.6%) with mean age of 48.3 ± 14.3 years completed all questionnaires. The average THI score was 9.2 ± 19.4, and 82.4% of patients reported to have slight tinnitus (THI ranged 0–16). The mean PSQI score was 8.4 ± 4.3, and 70.8% of participants had sleep difficulty (PSQI > 5). Compared with patients with slight tinnitus, those with catastrophic tinnitus were mostly old women with lower body mass index, and had higher scores in ESS, PSQI, and HADS (all P < 0.05). In 1140 patients with sleep difficulty, independent factors influencing THI were age, ESS, and HADS, and positive correlations were observed between age-adjusted THI and ESS, HADS-A, and HADS-D (all P < 0.001). Conclusion: Old age, daytime sleepiness, and psychological distress are highly associated with tinnitus severity among patients with sleep difficulty. Management of sleep disturbance and psychological distress is necessary to control tinnitus.